Preparation method of impact-resistant fiber composite board
By pretreating and hot-pressing the natural fibers and basalt fibers, combined with the use of modified chitosan, the problem of insufficient impact resistance of existing impact fiber composite sheets is solved, and higher mechanical properties and thermal insulation effect are achieved, and formaldehyde emission is reduced.
Patent Information
- Application Number
- CN202411674826.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The impact resistance performance of existing impact-resistant fiber composite sheets needs to be further improved.
By pretreating natural fibers and basalt fibers, a mixture of modified fibers and polypropylene was formed, loosened, combed, needle-punched, and hot-pressed in a hot-pressing mold, and finally impregnated and dried in modified chitosan to prepare impact-resistant fiber composite sheets with enhanced interface binding ability and improved mechanical properties.
It improves the mechanical properties of composite sheets, makes them more durable, and at the same time enhances the insulation effect and effectively reduces the concentration of formaldehyde in the air.
Smart Images

Figure CN119502409A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber composite boards, and in particular to a method for preparing an impact-resistant fiber composite board. Background Art
[0002] The Chinese patent with publication number CN112026213A discloses a method for manufacturing a super-strong bamboo fiber composite board, wherein bamboo fiber with an equivalent diameter of (0.2-0.5) mm and a length of (30-100) mm is blended with thermoplastic short fibers at a mass ratio of (70-30)% bamboo to (30-70)% plastic to form a blended rope, and then the blended powder is uniformly mixed at a mass ratio of (80-20)% thermoplastic powder to (20-80)% bamboo fiber powder to form a mixed powder. The invention uses the blended rope as a reinforcing rib and the mixed powder as a filler to produce a reinforced bamboo-plastic composite material, which breaks the application limitations of traditional bamboo materials, realizes the multifunctionality of bamboo fiber materials, and greatly improves its added value. However, the impact resistance of the composite board prepared by the above-mentioned prior art solutions needs to be further improved; to this end, the present invention provides a method for preparing an impact-resistant fiber composite board to solve the above-mentioned problem. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a method for preparing an impact-resistant fiber composite board, which solves the problems mentioned in the above background technology.
[0004] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing an impact-resistant fiber composite plate, comprising the following preparation steps:
[0005] Step 1: pretreating 10-20g of natural fiber and 25-45g of reinforced fiber;
[0006] Step 2: Mix the treated natural fiber, the reinforcing fiber and 55-70g of polypropylene, and then open, comb and needle punch in sequence;
[0007] Step 3: evenly lay them in a mold and perform hot pressing to obtain a fiber composite sheet, wherein the hot pressing temperature is 195°C, the hot pressing time is 12 minutes, and the hot pressing pressure is 10 MPa;
[0008] Step 4: immerse the fiber composite board in the modified chitosan, and then take it out and dry it.
[0009] Preferably, in step one, the pretreatment method for natural fibers is: pour the natural fibers into a vacuum tank, evacuate and maintain the vacuum degree at 0.08-0.1Mpa, maintain for 15-20 minutes, add the treatment agent, and continue to maintain the negative pressure for 5-8 minutes, then release the negative pressure in the tank and take it out, let it stand for 20-24 hours, wash it with anhydrous ethanol 2-4 times, and then place it in a drying oven at 70-80°C to dry to constant weight.
[0010] Preferably, the preparation method of the treating agent is: pour 0.8-1.5g of tetraethyl orthosilicate into a mixed solution of 45-60mL of anhydrous ethanol and deionized water, mix well, then add hydrochloric acid with a concentration of 0.1mol / L, and stir at room temperature for 45-60min.
[0011] Preferably, the volume ratio of anhydrous ethanol to deionized water is 0.8:(1-1.2).
[0012] Preferably, the natural fiber is selected from any one of straw fiber, cotton stalk fiber, poplar fiber, ramie fiber and bamboo fiber.
[0013] Preferably, in the step 1, the reinforcing fiber is basalt fiber, and the pretreatment method is: pour 60-75 mL of anhydrous ethanol into 2.5-4.5 g of KH550, stir evenly, add 30-50 g of basalt fiber, and soak for 25-30 minutes, then place it at room temperature for natural drying, and finally place it in a drying oven at 110-120° C. for 55-65 minutes.
[0014] Preferably, the preparation method of the modified chitosan is:
[0015] (1) 1.1-1.6 g of L-arginine, 1-1.2 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and 0.7-0.9 g of N-hydroxy-succinimide salt were sequentially poured into 100 mL of distilled water, and stirred in a water bath at 0-2° C. for 1.5-2 h to obtain Solution 1;
[0016] (2) Pour 1-1.8 g of chitosan into 100 mL of distilled water, add hydrochloric acid solution dropwise, and adjust the pH value of the solution to 5.2-5.8 to obtain Solution 2;
[0017] (3) Mix solution 1 and solution 2, and heat to 30-35°C in a water bath and react for 1.5-2h;
[0018] (4) adding sodium hydroxide solution dropwise to adjust the pH value of the solution to 7.8-8.0, thereby obtaining modified chitosan.
[0019] Preferably, in (2), the concentration of the hydrochloric acid solution is 0.1 mol / L; and in (4), the concentration of the sodium hydroxide solution is 1.0 mol / L.
[0020] Beneficial Effects
[0021] The present invention provides a method for preparing an impact-resistant fiber composite plate. Compared with the prior art, the method has the following beneficial effects:
[0022] (1) The method for preparing the impact-resistant fiber composite board comprises the following steps: modifying the basalt fiber to enhance the interface bonding ability between the basalt fiber and the matrix, thereby improving the mechanical properties of the composite board and making the composite board more durable; treating the natural fiber to form a layer of silica gel on its surface, thereby enhancing the mechanical meshing between the natural fiber and the matrix and improving the mechanical properties of the composite board; and the silica gel layer covers the surface of the natural fiber, thereby effectively improving the hardness and wear resistance of the natural fiber; the treated basalt fiber and the natural fiber work synergistically to enhance the thermal insulation effect of the board and at the same time make the fiber more evenly dispersed in the matrix, thereby improving the quality of the composite board.
[0023] (2) The preparation method of the impact-resistant fiber composite board material comprises modifying chitosan so that its molecular chain has abundant active groups such as hydroxyl and amino groups, which can increase the specific surface area and porosity of chitosan, thereby increasing the contact area with formaldehyde and enhancing the physical adsorption performance of formaldehyde, which can effectively reduce the concentration of formaldehyde in the air; secondly, it can chemically react with the functional groups on the surface of the fiber and the matrix material to form strong interactions such as covalent bonds or hydrogen bonds, thereby enhancing the bonding force between the fiber and the matrix and improving the mechanical properties of the composite board material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the fiber composite board of chitosan before and after surface spray modification provided by the present invention;
[0025] Figure 2 This is a comparison chart of formaldehyde emission test provided by the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] A method for preparing an impact-resistant fiber composite plate comprises the following preparation steps:
[0029] Step 1: Pre-treat cotton stalk fibers:
[0030] (1) Preparation of a treatment agent: Pour 0.8 g of tetraethyl orthosilicate into 45 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 0.8:1, mix well, then add 0.1 mol / L hydrochloric acid, and stir at room temperature for 45 min to obtain a treatment agent;
[0031] (2) Pour the cotton stalk fiber into a vacuum tank, evacuate and maintain the vacuum degree at 0.08 MPa for 15 minutes, add the treatment agent, and continue to maintain the negative pressure for 5 minutes, then release the negative pressure in the tank and take it out, let it stand for 20 hours, wash it twice with anhydrous ethanol, and then dry it in a drying oven at 70°C to constant weight;
[0032] Step 2: Pre-treat the basalt fiber: Pour 60 mL of anhydrous ethanol into 2.5 g of KH550, stir evenly, add 30 g of basalt fiber, and soak for 25 minutes, then place it at room temperature to dry naturally, and finally place it in a drying oven at 110°C to dry for 55 minutes;
[0033] Step 3: 10 g of the treated cotton stalk fiber, 25 g of the treated reinforcing fiber and 55 g of polypropylene are mixed, and then the mixture is opened, combed and needled in sequence;
[0034] Step 4: evenly lay them in a mold and perform hot pressing to obtain a fiber composite sheet, wherein the hot pressing temperature is 195°C, the hot pressing time is 12 minutes, and the hot pressing pressure is 10 MPa;
[0035] Step 5, preparation of modified chitosan: 1.1g of L-arginine, 1g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.7g of N-hydroxy-succinimide salt were sequentially poured into 100mL of distilled water, and stirred for 1.5h in a water bath at 0°C to obtain solution 1; 1g of chitosan was poured into 100mL of distilled water, and a hydrochloric acid solution with a concentration of 0.1mol / L was added dropwise, and the pH value of the solution was adjusted to 5.2 to obtain solution 2; solution 1 was mixed with solution 2, and the temperature was raised to 30°C in a water bath, and the reaction was carried out for 1.5h; a sodium hydroxide solution with a concentration of 1.0mol / L was added dropwise, and the pH value of the solution was adjusted to 7.8 to obtain modified chitosan;
[0036] Step 6: Immerse the fiber composite board in the modified chitosan, then take it out and dry it.
[0037] Example 2
[0038] A method for preparing an impact-resistant fiber composite plate comprises the following preparation steps:
[0039] Step 1: Pre-treat straw fiber:
[0040] (1) Preparation of a treatment agent: Pour 1.2 g of tetraethyl orthosilicate into 50 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 0.8:1.1, mix well, then add 0.1 mol / L hydrochloric acid, and stir at room temperature for 50 min to obtain a treatment agent;
[0041] (2) Pour the straw fiber into a vacuum tank, evacuate and maintain the vacuum degree at 0.09 MPa for 18 minutes, add the treatment agent, and continue to maintain the negative pressure for 6 minutes, then release the negative pressure in the tank and take it out, let it stand for 22 hours, wash it with anhydrous ethanol for 3 times, and then dry it in a drying oven at 75°C to constant weight;
[0042] Step 2: Pre-treat the basalt fiber: Pour 70 mL of anhydrous ethanol into 3.5 g of KH550, stir evenly, add 40 g of basalt fiber, and soak for 27 minutes, then place it at room temperature to dry naturally, and finally place it in a drying oven at 115°C to dry for 60 minutes;
[0043] Step 3: 15 g of the treated straw fiber, 35 g of the treated reinforcing fiber and 60 g of polypropylene are mixed, and then loosened, combed and needled in sequence;
[0044] Step 4: evenly lay them in a mold and perform hot pressing to obtain a fiber composite sheet, wherein the hot pressing temperature is 195°C, the hot pressing time is 12 minutes, and the hot pressing pressure is 10 MPa;
[0045] Step 5, preparation of modified chitosan: 1.3 g of L-arginine, 1.1 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.8 g of N-hydroxy-succinimide salt were sequentially poured into 100 mL of distilled water, and stirred for 1.8 h in a water bath at 1°C to obtain solution 1; 1.4 g of chitosan was poured into 100 mL of distilled water, and a hydrochloric acid solution with a concentration of 0.1 mol / L was added dropwise, and the pH value of the solution was adjusted to 5.5 to obtain solution 2; solution 1 was mixed with solution 2, and the temperature was raised to 32°C in a water bath, and the reaction was carried out for 1.7 h; a sodium hydroxide solution with a concentration of 1.0 mol / L was added dropwise, and the pH value of the solution was adjusted to 7.9 to obtain modified chitosan;
[0046] Step 6: Immerse the fiber composite board in the modified chitosan, then take it out and dry it.
[0047] Example 3
[0048] A method for preparing an impact-resistant fiber composite plate comprises the following preparation steps:
[0049] Step 1: Pre-treat ramie fiber:
[0050] (1) Preparation of a treatment agent: Pour 1.5 g of tetraethyl orthosilicate into 60 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 0.8:1.2, mix well, then add 0.1 mol / L hydrochloric acid, and stir at room temperature for 45 min to obtain a treatment agent;
[0051] (2) Pour the ramie fiber into a vacuum tank, evacuate and maintain the vacuum degree at 0.08 MPa for 15 minutes, add the treatment agent, and continue to maintain the negative pressure for 5 minutes, then release the negative pressure in the tank and take it out, let it stand for 20 hours, wash it twice with anhydrous ethanol, and then dry it in a drying oven at 70°C to constant weight;
[0052] Step 2: Pre-treat the basalt fiber: Pour 60 mL of anhydrous ethanol into 2.5 g of KH550, stir evenly, add 30 g of basalt fiber, and soak for 25 minutes, then place it at room temperature to dry naturally, and finally place it in a drying oven at 110°C to dry for 55 minutes;
[0053] Step 3: 10 g of the treated ramie fiber, 25 g of the treated reinforcing fiber and 70 g of polypropylene are mixed, and then the mixture is opened, combed and needled in sequence;
[0054] Step 4: evenly lay them in a mold and perform hot pressing to obtain a fiber composite sheet, wherein the hot pressing temperature is 195°C, the hot pressing time is 12 minutes, and the hot pressing pressure is 10 MPa;
[0055] Step 5, preparation of modified chitosan: 1.1g of L-arginine, 1g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.7g of N-hydroxy-succinimide salt were sequentially poured into 100mL of distilled water, and stirred for 1.5h in a water bath at 0°C to obtain solution 1; 1g of chitosan was poured into 100mL of distilled water, and a hydrochloric acid solution with a concentration of 0.1mol / L was added dropwise, and the pH value of the solution was adjusted to 5.2 to obtain solution 2; solution 1 was mixed with solution 2, and the temperature was raised to 30°C in a water bath, and the reaction was carried out for 1.5h; a sodium hydroxide solution with a concentration of 1.0mol / L was added dropwise, and the pH value of the solution was adjusted to 7.8 to obtain modified chitosan;
[0056] Step 6: Immerse the fiber composite board in the modified chitosan, then take it out and dry it.
[0057] Comparative Example 1
[0058] Compared with Example 1, the difference is that the natural fiber in Example 1 is not treated.
[0059] Comparative Example 2
[0060] Compared with Example 1, the difference is that the reinforcing fibers in Example 1 are not treated.
[0061] Comparative Example 3
[0062] Compared with Example 1, the difference is that the modified chitosan in Example 1 is replaced by chitosan.
[0063] Bending strength test: The test was conducted using an INSTRON-5582 universal strength tester in accordance with GB / T1449-2005; the results are shown in Table 1.
[0064] Tensile strength test: The test was conducted using a YC065 electronic fabric strength tester in accordance with GB / T1447-2005; the results are shown in Table 1.
[0065] Impact strength test: The test was conducted according to ASTM D256-2004; the results are shown in Table 1.
[0066] Table 1
[0067]
[0068] Formaldehyde emission test: Test in accordance with GB / T17657-2022.
[0069] like Figure 1 As shown in the figure, there are many pores of different sizes on the surface of the fiber composite board before spray modification of chitosan, which is the main channel for the release of formaldehyde and VOCs; after spraying modified chitosan, the surface of the fiber composite board is smooth and flat, and the pores are significantly reduced, which shows that the modified chitosan has good film-forming properties on the surface of the fiber composite board, can form a good shielding effect, and help reduce the release of formaldehyde and VOCs in the board.
[0070] like Figure 2 As shown, compared with Comparative Example 3, the amount of formaldehyde released by Examples 1-3 is significantly reduced.
[0071] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0072] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0073] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an impact-resistant fiber composite board, characterized in that: The method comprises the following preparation steps: Step 1: pretreating both natural fibers and reinforced fibers; Step 2: 10-20g of the treated natural fiber, 25-45g of the treated reinforcing fiber and 55-70g of polypropylene are mixed, and then the mixture is opened, combed and needled in sequence; Step 3: evenly lay them in a mold and perform hot pressing to obtain a fiber composite sheet, wherein the hot pressing temperature is 195°C, the hot pressing time is 12 minutes, and the hot pressing pressure is 10 MPa; Step 4: immerse the fiber composite board in the modified chitosan, and then take it out and dry it.
2. The method for preparing an impact-resistant fiber composite board according to claim 1, characterized in that: In the step 1, the pretreatment method for natural fibers is: pour the natural fibers into a vacuum tank, evacuate and maintain the vacuum degree at 0.08-0.1Mpa, maintain for 15-20 minutes, add the treatment agent, and continue to maintain the negative pressure for 5-8 minutes, then release the negative pressure in the tank and take it out, let it stand for 20-24 hours, wash it with anhydrous ethanol 2-4 times, and then place it in a drying oven at 70-80°C to dry to constant weight.
3. The method for preparing an impact-resistant fiber composite board according to claim 2, characterized in that: The preparation method of the treating agent is as follows: 0.8-1.5 g of tetraethyl orthosilicate is poured into a mixed solution of 45-60 mL of anhydrous ethanol and deionized water, mixed evenly, and then 0.1 mol / L of hydrochloric acid is added, and stirred at room temperature for 45-60 minutes.
4. The method for preparing an impact-resistant fiber composite board according to claim 3, characterized in that: The volume ratio of the anhydrous ethanol to deionized water is 0.8:(1-1.2).
5. The method for preparing an impact-resistant fiber composite board according to claim 1, characterized in that: The natural fiber is selected from any one of straw fiber, cotton stalk fiber, poplar fiber, ramie fiber and bamboo fiber.
6. The method for preparing an impact-resistant fiber composite board according to claim 1, characterized in that: In the step 1, the reinforcing fiber is basalt fiber, and the pretreatment method thereof is: pour 60-75 mL of anhydrous ethanol into 2.5-4.5 g of KH550, stir evenly, add 30-50 g of basalt fiber, and soak for 25-30 minutes, then place it at room temperature for natural drying, and finally place it in a drying oven at 110-120° C. for 55-65 minutes.
7. The method for preparing an impact-resistant fiber composite board according to claim 1, characterized in that: The preparation method of the modified chitosan is: (1) 1.1-1.6 g of L-arginine, 1-1.2 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and 0.7-0.9 g of N-hydroxy-succinimide salt were sequentially poured into 100 mL of distilled water, and stirred in a water bath at 0-2° C. for 1.5-2 h to obtain Solution 1; (2) Pour 1-1.8 g of chitosan into 100 mL of distilled water, add hydrochloric acid solution dropwise, and adjust the pH value of the solution to 5.2-5.8 to obtain Solution 2; (3) Mix solution 1 and solution 2, and heat to 30-35°C in a water bath and react for 1.5-2h; (4) adding sodium hydroxide solution dropwise to adjust the pH value of the solution to 7.8-8.0, thereby obtaining modified chitosan.
8. The method for preparing an impact-resistant fiber composite board according to claim 7, characterized in that: In (2), the concentration of the hydrochloric acid solution is 0.1 mol / L; in (4), the concentration of the sodium hydroxide solution is 1.0 mol / L.
Citation Information
Patent Citations
Manufacturing method of super-strong bamboo fiber composite board
CN112026213A